2019
DOI: 10.1167/tvst.8.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Assessment of Optic Nerves and Retina From a Patient With Chronically Implanted Argus II Retinal Prosthesis System

Abstract: Purpose To characterize histologic changes in the optic nerve and the retina of an end-stage retinitis pigmentosa (RP) patient after long-term implantation with the Argus II retinal prosthesis system. Methods Serial cross sections from the patient's both eyes were collected postmortem 6 years after implantation. Optic nerve from both eyes were morphometrically analyzed and compared. Retina underneath and outside the array was analyzed and compared with corresponding reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Possible causes of retinal damage include severe disease-related degeneration, damage to the retina as a result of surgical implantation, or damage caused by the presence of the array. A variety of studies have found evidence suggestive of retinal damage in retinal prosthesis patients ( Gregori et al, 2018 ; Lin et al, 2019 ; Rizzo et al, 2019 ; Patelli et al, 2020 ). This damage seems to have a variety of causes including inflammation, “boggy” ( sic ) thickening, schisis and fibrosis, intraretinal fluid (IRF) cysts, as well as a “snowplow” effect of the electrode array pressing against the retina and causing adjacent thickening ( Gregori et al, 2018 ; Patelli et al, 2020 ).…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible causes of retinal damage include severe disease-related degeneration, damage to the retina as a result of surgical implantation, or damage caused by the presence of the array. A variety of studies have found evidence suggestive of retinal damage in retinal prosthesis patients ( Gregori et al, 2018 ; Lin et al, 2019 ; Rizzo et al, 2019 ; Patelli et al, 2020 ). This damage seems to have a variety of causes including inflammation, “boggy” ( sic ) thickening, schisis and fibrosis, intraretinal fluid (IRF) cysts, as well as a “snowplow” effect of the electrode array pressing against the retina and causing adjacent thickening ( Gregori et al, 2018 ; Patelli et al, 2020 ).…”
Section: Modelingmentioning
confidence: 99%
“…This damage seems to have a variety of causes including inflammation, “boggy” ( sic ) thickening, schisis and fibrosis, intraretinal fluid (IRF) cysts, as well as a “snowplow” effect of the electrode array pressing against the retina and causing adjacent thickening ( Gregori et al, 2018 ; Patelli et al, 2020 ). While many of these conditions are common in late stage RP patients, they seem to be exacerbated in the implanted eye ( Lin et al, 2019 ). In addition, over time many patients also develop membranes (both adherent to and separated from the retina) between the retina and the array.…”
Section: Modelingmentioning
confidence: 99%
“…These conflicting results may be explained because the RGC population was analyzed too early (before a complete loss of photoreceptors had occurred [100,101]), which is a prerequisite for axonal compression and the sensibility of the techniques applied to identify and/or quantify the RGC population that occur in localized sectors, which could be missed by other authors [53]. Studies performed in humans have documented RGC loss in human patients with photoreceptor degenerations [102,103,104,105,106,107,108].…”
Section: Retinal Remodeling and Retinal Ganglion Cellsmentioning
confidence: 99%
“…However, the treatment was applied before complete photoreceptor loss and therefore further studies are needed to clarify this fact. In addition, the glial seal formed by Müller cells may also contribute to the failure of attempts to replace lost photoreceptors [52,106], for example limiting the migration of transplanted cells [113] and perhaps the creation of new synaptic connections.…”
Section: Retinal Remodeling and Retinal Ganglion Cellsmentioning
confidence: 99%
“…1 Furthermore, a recent study provided histopathologic evidence supporting the long-term safety of Argus II retinal implant using morphometric analysis. 2 The basic idea behind Argus II is to electrically stimulate the surviving ganglion cells in the retina to elicit visual percepts. However, it requires more than just perception of phosphenes to have any comprehensible visual experience.…”
Section: Introductionmentioning
confidence: 99%